(untitled) (ENTHYMEMA, 2012)
This work offers a study of the musical characterization of Tres lecciones de tinieblas (1980) by José Ángel Valente (1929-2000). This is done, first, by the analysis of poetic keys provided by the author in various texts (interviews, essays, speeches, diary ...) so, subsequently, identify the sources of the poems, whether musical –from Gregorian chant to Webern, Boulez or Schenker–, literary (Gonzalo de Berceo, etc.), philosophical (Miguel de Molinos) ... In all models presented excels, in particular, the assimilation by Valente of the genre of Leçons Ténèbres –especially Couperin and Charpentier–, as well as of the tradition of Spanish Golden age, with echoes of Tomás Luis de Victoria, Quevedo and his Lágrimas de Hieremías castellanas, the “silent music” of San Juan de la Cruz or the “musical poetry” of Gongora, among other flagship references. Finally, given the complex nature generic of Tres lecciones, we study with special attention, in short, both the Pythagorean symbolism as the musical properties of the letters-numbers to conclude with some notes on the poetics of the fragment.